Effect of aging on glucose homeostasis: Accelerated deterioration of β-cell function in individuals with impaired glucose tolerance - Szoke, Ervin; Shrayyef, Muhammad Z.; Messing, Susan; Woerle, Hans J.; Van Haeften, Timon W.; Meyer, Christian; Mltrakou, Asimina; Pimenta, Walkyria; Gerich, John E. (American Diabetes Association, 2008)
OBJECTIVE -To examine the effect of aging on insulin secretion (first- and second-phase insulin release) and insulin sensitivity in people with normal glucose tolerance (NGT) or impaired glucose tolerance (IGT). RESEARCH DESIGN AND METHODS- First- and second-phase insulin secretion and insulin sensitivity were assessed in hyperglycemic clamp experiments in 266 individuals with NGT and 130 individuals with IGT, ranging in age from ∼20 to ∼70 years. Changes in β-cell function were compared using the disposition index to adjust for differences in insulin sensitivity. RESULTS -As expected, both phases of insulin release and insulin sensitivity were reduced in individuals with IGT (all P < 0.01). Insulin sensitivity was not independently correlated with age in either group. In people with NGT, the disposition index for first-and second-phase insulin release decreased similarly at a rate of ∼0.7% per year. In people with IGT, the disposition indexes for first-and second-phase insulin release decreased at greater rates (∼2.2 and 1.4% per year, P = 0.002 and 0.009, respectively, vs. NGT), with the decrease in first phase being greater than that of second phase (P = 0.025). CONCLUSIONS -Insulin secretion (both first and second phase) normally decreases at a rate of ∼ 0.7% per year with aging; this decrease in β-cell function is accelerated about two-fold in people with impaired glucose tolerance-first phase to a greater extent than second phase. Finally, aging per se has no effect on insulin sensitivity independent of changes in body composition. © 2008 by the American Diabetes Association.